Drawing Noise - Ivan Elezovic (Journal of the Association for Technology in Music Instruction, 2025)
DRAWING NOISE is a collaboration between a painter, a composer, and a photographer-video artist. The main intention is to further explore the ambient music that painting and drawing produce. The approach of audio is correlated with the sounds of various hand-movements by color pens on textured drywall. The method of making and designing audio and visual documentation of the creation of the wall drawings serve as the raw material for the final video. The audio in the project originates from recorded artistic performance that portrays a series of circle-shape objects in real time. Furthermore, various layers of sounds are added into recorded material that enhance and enrich the spectral environment. Thus, a noise-like audio effect predominates within the project. Finally, the intention to continue pursuing an ongoing collaboration came out of fascination about the possibilities of integrating multiple artistic disciplines to explore other methods of structuring artistic works.
Keywords: composition